Chronic exposure to the mycotoxin T‐2 promotes oral absorption of chlortetracycline in pigs. Issue 6 (24th May 2013) - Goossens, J.; Devreese, M.; Pasmans, F.; Osselaere, A.; De Baere, S.; Verbrugghe, E.; Haesebrouck, F.; De Backer, P.; Croubels, S.
Abstract : The aim of this study was to investigate whether T‐2 toxin, a potent Fusarium mycotoxin, affects the oral absorption of the antibiotic chlortetracycline in pigs. Animals were allocated to blank feed without T‐2 toxin (controls), feed containing 111 μg T‐2/kg feed, T‐2‐contaminated feed supplemented with a yeast‐derived feed additive, or blank feed supplemented solely with the feed additive, respectively. After 21 days, an intragastric bolus of chlortetracycline was given to assess potential alterations in the pharmacokinetics of this commonly used antibiotic. A significantly higher area under the plasma concentration–time curve and maximal plasma concentration of chlortetracycline was observed after intake of T‐2‐contaminated feed compared with control. Thus, exposure to T‐2‐contaminated feed can influence the oral bioavailability of chlortetracycline. This effect could have consequences for the withdrawal time of the drug and the occurrence of undesirable residues in edible tissues.